Partial-Volume Effect on Ischemic Tissue-Fate Delineation Using Quantitative Perfusion and Diffusion Imaging on a Rat Stroke Model - Ren, Hongxia (2004)
Partial-volume effects (PVE) in stroke imaging could hinder proper delineation of normal, ischemic, and at-risk tissues. Cerebral-blood-flow (CBF) and apparent diffusion coefficient (ADC) were measured at high and low resolution (HR = 128 × 128, LR = 64 × 64) in focal ischemia in rats during the acute phase. The data were evaluated for PVE on ischemic tissue classification on a pixel-by-pixel basis and the misclassified pixels were quantified as ischemia progressed. The main drawbacks of high-resolution imaging are reduced temporal resolution and/or signal-to-noise ratio. The high- versus low-resolution scatterplots and histograms of pixels along the normal–abnormal boundaries in the ADC and CBF maps showed marked ischemia-related PVE. By comparison with the homologous regions in the contralateral normal hemisphere, the effect of increased noise and intrinsic tissue heterogeneity due to high resolution could be distinguished from ischemia-related PVE. Degrading the high-resolution (128 × 128) data to a 64 × 64 or 32 × 32 matrix increased the severity of PVE. Zero-filling of low-resolution (64 × 64) data to 128 × 128 also increased PVE. It was concluded that PVE: (1) misclassified substantial pixels along the normal–abnormal boundaries, (2) overestimated abnormal volumes at the expense of mostly “at-risk” and some “normal” tissues, (3) were more severe at the early time points postischemia, and (4) confounded the interpretation of the operationally defined ischemic penumbra.